2014
DOI: 10.1590/0037-8682-0222-2013
|View full text |Cite
|
Sign up to set email alerts
|

Indeterminate RIBA results were associated with the absence of hepatitis C virus RNA (HCV-RNA) in blood donors

Abstract: Introduction: Hepatitis C virus (HCV) infection is diagnosed by the presence of antibodies and is supplemented by confi rmatory testing methods, such as recombinant immunoblot assay (RIBA) and HCV-RNA detection. This study aimed to evaluate the effi cacy of RIBA testing to diagnose HCV infection in blood donors positive for anti-HCV antibodies. Methods: A total of 102 subjects positive for anti-HCV determined by enzyme-linked immunosorbent assay (ELISA) at the Hematology and Hemotherapy Foundation of Bahia (HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
(17 reference statements)
4
11
0
Order By: Relevance
“…We found that the majority of RIBA indeterminates in presumably uninfected subjects presented antibodies that bind to HCV NS3 peptides. Similar results have been reported previously by Pereira et al [ 9 ] who found anti-NS3 antibodies (86 %; 12/14) and anti-core antibodies (14 %; 2/14) when examining blood donors.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We found that the majority of RIBA indeterminates in presumably uninfected subjects presented antibodies that bind to HCV NS3 peptides. Similar results have been reported previously by Pereira et al [ 9 ] who found anti-NS3 antibodies (86 %; 12/14) and anti-core antibodies (14 %; 2/14) when examining blood donors.…”
Section: Discussionsupporting
confidence: 91%
“…However, among populations with low (<10 %) prevalence of HCV infection, assays for anti-HCV antibodies show high false-positive rates [ 11 ] which require confirmation with other more specific supplementary tests. Recombinant immunoblot assay is the preferred supplementary serological testing method due to its robust specificity [ 9 , 12 , 13 ]. According to the 2003 Centers for Disease Control and Prevention (CDC) guidelines, positive anti-HCV screening results should be confirmed using RIBA to confirm positive screening results and differentiate false positivity from true HCV exposure [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, anti‐HCV IB assays can generate indeterminate results, defined by the manufacturer as band reactivity that is insufficient to meet the criteria for a positive result. Interpreting the significance of IB indeterminate results can be difficult as HCV RNA is usually not detectable and such results may represent either past exposure to HCV or non‐specific reactivity . In a previous study of Australian blood donors with indeterminate results on the RIBA 3·0 HCV strip IB assay (Chiron Corp., Emeryville, CA, USA), a number of indicators of past exposure to HCV were identified which included the sample to cut‐off (s/co) ratio of the screening IA, IB band reactivity, risk factors for HCV infection and donation history .…”
Section: Introductionmentioning
confidence: 99%
“…HCV infections are a serious public health issue, with approximately 160‐170 million people infected worldwide, and early detection and treatment are key for preventing its transmission and providing effective treatment. Currently, anti‐HCV testing remains the preferred screening tool for HCV infections, but it is not sensitive during the window period of infections and hemodialysis; false positives are often observed in pregnancy and patients with autoimmune diseases, and it also cannot distinguish between active and past HCV infections . HCV RNA detection is used to confirm and manage antiviral therapy for HCV infections.…”
Section: Introductionmentioning
confidence: 99%